On the nonlinear interactions and existence of breathers in a chain of coupled pendulums. (September 2017) - Ture Savadkoohi, A.; Lamarque, C.-H.; Goutte, J.D.
Abstract: The paper considers a chain of linearly coupled pendulums. Continues first order system equations are treated via time and space multiple scale method which lead to nonlinear Schrödinger equation. Further investigations on the nonlinear Schrödinger equation detects systems responses in the form of propagated nonlinear waves as functions of their envelope and phases. This provides information about localization of nonlinear waves and their directions in space and time. Abstract : Highlights: 1. We study dynamics of a chain of linearly coupled pendulums. 2. Discrete form of system equations are derived. 3. First order expansion of equations leads to nonlinear Schrödinger equation. 4. Tracing localized solitons in space leads to phase and envelope of the propagation. 5. The system can be used for passive control/energy harvesting.